2021
DOI: 10.1186/s12864-021-07781-1
|View full text |Cite
|
Sign up to set email alerts
|

LABRAT reveals association of alternative polyadenylation with transcript localization, RNA binding protein expression, transcription speed, and cancer survival

Abstract: Background The sequence content of the 3′ UTRs of many mRNA transcripts is regulated through alternative polyadenylation (APA). The study of this process using RNAseq data, though, has been historically challenging. Results To combat this problem, we developed LABRAT, an APA isoform quantification method. LABRAT takes advantage of newly developed transcriptome quantification techniques to accurately determine relative APA site usage and how it vari… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 91 publications
1
40
0
Order By: Relevance
“…The association between distal PAS usage and localization of transcripts to projections of migrating cells was also observed in NIH3T3 and MDA-MB231 cells (Goering et al, 2021). Further, it was demonstrated that the use of distal PAS in both tandem UTR and ALE structures was associated with localization to cellular projections (Goering et al, 2021).…”
Section: Apa In Neuronsmentioning
confidence: 76%
See 2 more Smart Citations
“…The association between distal PAS usage and localization of transcripts to projections of migrating cells was also observed in NIH3T3 and MDA-MB231 cells (Goering et al, 2021). Further, it was demonstrated that the use of distal PAS in both tandem UTR and ALE structures was associated with localization to cellular projections (Goering et al, 2021).…”
Section: Apa In Neuronsmentioning
confidence: 76%
“…General trends of RNA localization to membranes and 3′ end choice have been revealed by LABRAT, an APA quantification software (Goering et al, 2021). LABRAT analysis of biochemical fractionations derived from three different cell types (Benoit Bouvrette et al, 2018) revealed that longer (more distal APA) transcripts are enriched in the membrane-associated fraction (Figure 2B) (Goering et al, 2021).…”
Section: Apa and Rna Localization To Membranesmentioning
confidence: 91%
See 1 more Smart Citation
“…4 A ). The relative usage of these APA isoforms in our RNA-seq libraries was analyzed using lightweight alignment-based reckoning of alternative three-prime ends (LABRAT) ( 21 ), which generated a ψ score (ranging from 0 to 1) for each gene in each genotype. Lower ψ values indicate preferential use of proximal PASs and higher values indicate preferential use of distal PASs.…”
Section: Resultsmentioning
confidence: 99%
“…RNA-seq reads were trimmed and pseudoaligned to the transcriptome, and differential expression was analyzed using sleuth ( 44 ). Customized reference transcripts and PACs were used by LABRAT to analyze PAS usage ( 21 ). Detailed methods are provided in the SI Appendix , Supplementary Text .…”
Section: Methodsmentioning
confidence: 99%